The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/em.21857
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental effects of UV‐B radiation in a xeroderma pigmentosum‐variant cell line

Abstract: DNA polymerase η (pol η), of the Y-family, is well known for its in vitro DNA lesion bypass ability. The most well-characterized lesion bypassed by this polymerase is the cyclobutane pyrimidine dimer (CPD) caused by ultraviolet (UV) light. Historically, cellular and whole-animal models for this area of research have been conducted using UV-C (λ = 100–280 nm) owing to its ability to generate large quantities of CPDs and also the more structurally distorting 6-4 photoproduct. Although UV-C is useful as a laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 42 publications
1
13
0
2
Order By: Relevance
“…Similarly, untreated NHF cells gave a MF value of 0.55 × 10 −5 , with MD (1.65 × 10 −5 ; 3×) and MBL (1.27 × 10 −5 ; 2.4×) again causing very little difference. This is in comparison to our previously published work using environmentally relevant levels of UV-B (10 mJ/cm 2 ) in which the MF of XP-V cells was 25.8 × 10 −5 (26× higher than untreated) and for NHF cells the MF was 8.56 × 10 −5 (15.6× untreated) [18]. In addition, we attempted alternative treatment protocols in an attempt to exacerbate the effects, in case a single, short oxidative stress inducing treatment was insufficient to generate damage/mutations at levels detectable in this assay.…”
Section: Evaluation Of Nuclear Mutations Using the Hprt Locussupporting
confidence: 50%
See 1 more Smart Citation
“…Similarly, untreated NHF cells gave a MF value of 0.55 × 10 −5 , with MD (1.65 × 10 −5 ; 3×) and MBL (1.27 × 10 −5 ; 2.4×) again causing very little difference. This is in comparison to our previously published work using environmentally relevant levels of UV-B (10 mJ/cm 2 ) in which the MF of XP-V cells was 25.8 × 10 −5 (26× higher than untreated) and for NHF cells the MF was 8.56 × 10 −5 (15.6× untreated) [18]. In addition, we attempted alternative treatment protocols in an attempt to exacerbate the effects, in case a single, short oxidative stress inducing treatment was insufficient to generate damage/mutations at levels detectable in this assay.…”
Section: Evaluation Of Nuclear Mutations Using the Hprt Locussupporting
confidence: 50%
“…Abbreviations: CFE, colony forming efficiency; MF, mutation frequency. Data for untreated samples are the same as previously reported [18]. frequency (MF) of 0.98 × 10 −5 .…”
Section: Evaluation Of Nuclear Mutations Using the Hprt Locusmentioning
confidence: 99%
“…Mutational effects by UVA are typically due to lesions induced by direct DNA absorption (pyrimidine dimers). Most of the published studies have reported C > T changes at dipyrimidine sites (Robert et al, 1996;Ikehata et al, 2003;Agar et al, 2004;Kappes et al, 2006), which is similar to UVC and UVB induced mutagenesis (Brash et al, 1987;Douki et al, 2003;Kappes et al, 2006;Herman et al, 2014). Interestingly, this type of mutation has been detected in nonmelanoma (Giglia-Mari and Sarasin, 2003), as well as, melanoma skin cancers (Greenman et al, 2007;Pleasance et al, 2010).…”
Section: Dna Glycosylase Neil1 Binds and Excises Psoraleninduced Monomentioning
confidence: 76%
“…Exposure of cultured cells to UV irradiation proved that UV‐C (100–280 nm) is more useful than UV‐B (280–315 nm) because of UV‐C's ability to generate large quantities of cyclobutane pyrimidine dimers (CPD) and is also a more structurally distorting 6–4 photoproduct . Herman et al . reported that UV‐B has similar but less striking effects than UV‐C concerning both its cytotoxic and mutagenic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of cultured cells to UV irradiation proved that UV-C (100-280 nm) is more useful than UV-B (280-315 nm) because of UV-C's ability to generate large quantities of cyclobutane pyrimidine dimers (CPD) and is also a more structurally distorting 6-4 photoproduct. 30 Herman et al 31 reported that UV-B has similar but less striking effects than UV-C concerning both its cytotoxic and mutagenic effects. In the present study, we aimed to differentiate each XP group by complementation assays using recombinant adenoviruses, and found that both UV-B and UV-C were useful for differentiation of XP groups but UV-C showed a clearer separation between surviving cells after infection of matched recombinant adenoviruses and those of unmatched viruses (Fig.…”
Section: Discussionmentioning
confidence: 99%